Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan PT Pertamina Patra Niaga Integrated Terminal Banjarmasin - Ellybina Awaliya Rahmah; Irwansyah; Hairudinor; Noor Hidayati (Smart Business Journal (SBJ), 2026)
May 20, 2026: Rahmah, Ellybina Awaliya, 2210412320009. How workers at PT Pertamina Patra Niaga Integrated Terminal Banjarmasin are affected by their work motivation and the way their bosses lead them. under the charge of Irwansyah. An organization's success depends on its employees' performance. Two of the many elements that effect productivity are a leader's style and staff motivation. This study examines the major effects of leadership style and work drive on PT Pertamina Patra Niaga Integrated Terminal Banjarmasin workers' performance. It employed quantitative methodologies and saturation sampling to encompass all 50 employees. Multiple linear regression was utilized in SPSS 25. The study found no influence of leadership style on PT Pertamina Patra Niaga Integrated Terminal Banjarmasin employee performance. Work drive affects PT Pertamina Patra Niaga Integrated Terminal Banjarmasin employees. Leadership style and work ethics affect PT Pertamina Patra Niaga Integrated Terminal Banjarmasin staff performance. KEYWORDS: Leadership Style, Work Motivation, Employee Performance